Non-engineered and Engineered Adult Neurogenesis in Mammalian Brains - Lei, Wenliang; Li, Wen; Ge, Longjiao; Chen, Gong (Frontiers in Neuroscience, 2019)
Adult neurogenesis has been extensively studied in rodent animals, with distinct niches found in the hippocampus and subventricular zone (SVZ). In non-human primates and human postmortem samples, there has been heated debate regarding adult neurogenesis, but it is largely agreed that the rate of adult neurogenesis is much reduced comparing to rodents. The limited adult neurogenesis may partly explain why human brains do not have self-repair capability after injury or disease. A new technology called “in vivo cell conversion” has been invented to convert brain internal glial cells in the injury areas directly into functional new neurons to replenish the lost neurons. Because glial cells are abundant throughout the brain and spinal cord, such engineered glia-to-neuron conversion technology can be applied throughout the central nervous system (CNS) to regenerate new neurons. Thus, compared to cell transplantation or the non-engineered adult neurogenesis, in vivo engineered neuroregeneration technology can provide a large number of functional new neurons in situ to repair damaged brain and spinal cord.